Linguistic Phenomena in the Context of Psycholinguistic Analysis - Oripova, Nargiza Vosiqjon Qizi (PT. Antis International Publisher, 2024)
In the article, analysis and generalization of theoretical and experimental data on the study of human speech behavior allow us to conditionally distinguish the following three aspects in the structure of language ability: the language mechanism or the ability to master a language (native and / or foreign), the language organization of a person or mental representation and organization in the mind of the speaker systems of signs of a natural language and the norms of their communication, the speech mechanism or the ability to carry out speech activity - to produce and perceive speech statements.